Incorporation of drug-resin complex to improve microsphere performance - Jadhav, Namdeo R; Bhakare, Hitesh R; Bhawale, Badrinath K (Asian Journal of Pharmaceutics (AJP), 2014)
The objective of present work was to incorporate drug-resin complex (DRC) to microspheres to achieve improved drug loading, less leakage, and extended zero order release. Ondensetron hydrochloride (ODH), a model drug was complexed with Indion 244, and incorporated to microspheres of hydroxypropyl methyl cellulose (HPMC), and ethyl cellulose (EC). A 32 full factorial design was used to prepare microspheres using HPMC and EC as independent variables, X1 and X2 respectively.The microspheres obtained were evaluated for yield, topology, micromeritics, drug entrapment, and drug release kinetics. Complexation of ODH with Indion 244 was found to be 28% wt/wt. The incorporation efficiency of DRC to microspheres (DRC1-DRC9) was in the range of 70.41 ± 2.18 to 95.08 ± 0.76% wt/wt. The trend of increase in the drug entrapment (DRC) with high amounts of HPMC and EC was noted for all microspheres. Yield of DRC9 was maximum (84.87% wt/wt), and was lowest for DRC1. Acceptable Hausner’s ratio, Carr’s compressibility index and angle of repose demonstrated the excellent flowability of microspheres (DRC1 to DRC9). Drug release kinetic studies showed that, ODH dissociation from DRC, and its diffusion through HPMC and EC, both, have contributed for extended zero order release. Especially, from DRC2, maximum extended release was noted up to 19.10 hrs (zero order, R2 = 0.9239). Hence, it can be concluded that, incorporation of DRC to microspheres can overcome poor drug loading, high drug leakage, and poor drug sustainability problems of microspheres. Especially, the zero order release can be achieved by incorporation of DRC to microspheres.